Barriers and facilitators of domain-specific physical activity: a systematic review of reviews - Leandro Garcia; Gerfeson Mendonça; Tânia R. Bertoldo Benedetti; Lucélia Justino Borges; Inês Amanda Streit; Marina Christofoletti; Fernando Lopes e Silva-Júnior; Camila Bosquiero Papini; Maria Angélica Binotto (BMC, 2022)
Abstract Background Knowing what facilitates and hinders physical activity behaviour across domains (leisure, travel, work or education, and household) is central for the development of actions for more active lifestyles. Thus, the aim of this systematic review of reviews was to summarize the evidence on barriers and facilitators of domain-specific physical activity. Methods We included systematic reviews with or without meta-analysis that investigated the association between modifiable barriers and facilitators and levels of domain-specific physical activity. Reviews published until September 2020 were retrieved from PubMed, ISI Web of Science, Scopus, Regional Library of Medicine (BIREME), and PsycNET, and from the reference list of selected articles. Each review was screened by two independent reviewers for eligibility. Data extracted from selected papers included methodological aspects (number of primary studies, study designs, and age groups); physical activity domains and barriers and facilitators investigated; and direction of association. For each pair of barrier/facilitator and domain-specific physical activity, we recorded the number of positive, negative, and null associations reported across reviews. Quality assessment of each systematic review was performed using the AMSTAR-2 tool. Results Forty-four systematic reviews were selected. The evidence base was largest for leisure-time followed by travel-related physical activity. A very small number of reviews included physical activity in work, educational and domestic settings. Across all physical activity domains, factors related to the built environment were more abundant in the reviews than intra and interpersonal factors. Very consistent positive associations were observed between a range of intrapersonal factors and leisure-time physical activity, as well as moderately consistent evidence of positive association for general social support and support from family members. Evidence of moderate consistency was found for the positive association between transport-related physical activity and positive beliefs about consequences, walkability, and existence of facilities that support active travel. Evidence on barriers and facilitators for physical activity at work, educational, and domestic settings was limited in volume and consistency. Conclusions Efforts and resources are required to diversify and strength the evidence base on barriers and facilitators of domain-specific physical activity, as it is still limited and biased towards the leisure domain and built environment factors. Trial registration PROSPERO CRD42020209710.